199k views
4 votes
how do you find the length of the hypotenuse when you have only the length of the altitude of the hypotensuse and a length of a leg?

User Toine Db
by
5.1k points

1 Answer

4 votes

Answer:

By using The Pythagorean Theorem:


/Hypotenuse/^(2) = /Length of altitude/^(2) + /Length of leg/^(2) \

/Hypotenuse/ =
\sqrt\ /Length of altitude/^(2) + /Length of leg/^(2) \}

Explanation:

The Pythagorean theorem states that: Given a Right-angled triangle, the square of the hypotenuse equals the sum of squares of the other two sides ( Here, being the length of the altitude and length of leg). That is,


/Hypotenuse/^(2) = /Length of altitude/^(2) + /Length of leg/^(2) \ and hence,

/Hypotenuse/ =
\sqrt\ /Length of altitude/^(2) + /Length of leg/^(2) \}

For example, If the length of the altitude is 4m and the length of leg is 3m. Using The Pythagorean theorem, the length of the hypotenuse will be


/Hypotenuse/^(2) = /Length of altitude/^(2) + /Length of leg/^(2) \\\/Hypotenuse/ = \sqrt{/Length of altitude/^(2) + /Length of leg/^(2)} \\/Hypotenuse/ = \sqrt{4^(2) + 3^(2) }


/Hypotenuse/ = √(16+9) \\/Hypotenuse/ = √(25) \\/Hypotenuse/ = 5m

The length of the hypotenuse for the given example will be 5m.

This is how to find the length of an hypotenuse.

User Sanjay Yadav
by
5.3k points